Sosialisasi implementasi gerakan literasi sekolah di SMP Al Falah, Pondok Melati,Bekasi. - Prameswari, Jatut; Sumadyo, Bambang; Susanti, Dewi Indah (Presisi Jurnal Pengabdian Masyarakat, 2022)
Literacy is no longer a new thing in our world of education. Where literacy should have become a culture not only for students, but also for educators. Literacy itself is an activity of habitual thinking which is also followed by a reading-writing process and will eventually lead to critical thinking, problem solving, scientific development, and the creation of a work. The school literacy movement (GLS) itself is an implementation of the Minister of Education and Culture Regulation Number 23 of 2015 concerning "Business Character Development". Based on the Minister of Education Regulation, this GLS activity is certainly very important for the progress of education in schools. In addition, GLS provides many positive impacts for the students themselves. Progress of critical thinking and being able to create a scientific work. For this reason, socialization about GLS needs to be done to help teachers know more about GLS itself so that they are able to optimally implement literacy movement activities at Al Falah Junior High School.